Hyperbaric oxygen ameliorates cognitive impairment in patients with Alzheimer's disease and amnestic mild cognitive impairment - Jianwen Chen; Feng Zhang; Li Zhao; Cheng Cheng; Rujia Zhong; Chunbo Dong; Weidong Le (Alzheimer’s & Dementia: Translational Research & Clinical Interventions, 2020)
Abstract Introduction It has been reported that environmental factors such as hypoxia could contribute to the pathogenesis of Alzheimer's disease (AD). Therapeutics like hyperbaric oxygen treatment, which improves tissue oxygen supply and ameliorates hypoxic conditions in the brain, may be an alternative therapy for AD and amnestic mild cognitive impairment (aMCI). The present work aims to investigate the potential therapeutic effect of hyperbaric oxygen treatment for AD and aMCI. Methods We recruited 42 AD, 11 aMCI, and 30 control AD patients in this study. AD and aMCI patients were treated with 40 minutes of hyperbaric oxygen once a day for 20 days and assessed by neuropsychiatric assessments including Mini‐Mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA), and Activities of Daily Living (ADL) scale before and at 1‐, 3‐, and 6‐month follow‐up after treatment. Control AD patients who were not given hyperbaric oxygen treatment had similar clinical profile as hyperbaric oxygen treated AD. We examined 10 of the AD/aMCI patients with fluorodeoxyglucose positron emission tomography. Results In self‐comparison study, one course of hyperbaric oxygen treatment significantly improved the cognitive function assessed by MMSE and MoCA in AD patients after 1‐month follow‐up; such treatment also significantly improved MMSE score at 3‐month follow‐up and MoCA score at 1‐ and 3‐month follow‐up in aMCI patients. The ADL scale was significantly improved in AD patients after 1‐ and 3‐month follow‐up. Compared to the control AD patients, the MMSE and MoCA in hyperbaric oxygen treated AD patients were significantly improved after 1‐month follow‐up. Hyperbaric oxygen treatment also ameliorated the reduced brain glucose metabolism in some of the AD and aMCI patients. Conclusion Based on previous studies and our recent findings, we propose that hyperbaric oxygen treatment may be a promising alternative therapy for AD and aMCI.